Quadrotor aircraft attitude control algorithm based on improved UKF. Issue 4 (February 2019) - Chen, Xiaofei; Zhang, Gang; Lu, Chengling; Cheng, Junhui
Abstract: The quadrotor aircraft attitude estimation algorithm which is based on the adaptive attenuation memory unscented Kalman filter algorithm is proposed. The UKF algorithm uses the quaternion method to solve the attitude. The drift output of the gyroscope amplified as part of the state variable, and the attitude angle is used as the measurement variable to establish a filtering model, which effectively suppresses the attitude error caused by the gyro drift. The attenuation memory filter and adaptive algorithm are introduced based on the UKF algorithm to solve the problem of the accuracy degradation of the system model when it is abnormally interfered. The filter divergence is suppressed and the robustness and stability of the system are improved. The simulation results show that the algorithm can effectively improve the attitude estimation accuracy of the aircraft compared with the traditional UKF algorithm.